Segmen Feature dalam Program Berita Jawa Tengah Hari Ini di TVRI Jawa Tengah - Rizky Alisha Rahma; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Television is a mass media which until now is still in the highest order of consumeed by the public. Television as a mass media presents a variety of entertaining and informative that shows so that many television stations compete to present quality broadcast programs. The development of television broadcast quality also makes local television take part in competing to present programs that are liked by the public. One of them is TVRI Central Java, which is currently rebranding with the aim of attracting a wider audience such as the millennial generation. TVRI Jawa Tengah, with an effort to expand the reach of the audience by giving priority to news and information programs that are quality, educational and liked by the public. One of the shows that are of interest is a feature. Universitas Diponegoro’s journalism work presents a feature segment for the news program Jawa Tengah Hari Ini on TVRI Jawa Tengah. The feature segment will discuss themes around the community / hobbies, culinary and tourism. During the production process the writer plays several job descriptions such as producer, reporter, scriptwriter, cameraman and video editor. Job desk is divided according to the theme of coverage. The feature segment airs at the end of the Central Java Today segment, presenting 48 segments. Starts airing on July 27 to November 2 2020 with duration of 3-5 minutes. During the production process, of course, there are different obstacles in each segment. Through this feature segment, it is hoped that it can present informative and educational shows and can be used as entertainment during the Covid-19 pandemic. The impressions presented by this work in journalism can also be a contribution of communication students to the local television industry.